2006
DOI: 10.1111/j.1464-410x.2006.06401.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the psychosocial impact of population‐based prostate‐specific antigen testing for prostate cancer in the UK

Abstract: OBJECTIVE To evaluate the psychosocial impact of participation in a population‐based prostate‐specific antigen (PSA) testing programme, akin to screening, and to explore the relationship between urinary symptoms reported before PSA testing and the response to the subsequent PSA result. PATIENTS AND METHODS This prospective questionnaire study was nested within the case‐finding component of the ProtecT (prostate testing for cancer and treatment) feasibility study (ISRCTN20141297). Men aged 50–69 years from 18 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 26 publications
4
33
0
Order By: Relevance
“…The level as well as prevalence of depression was lower than of anxiety, with the prevalence of anxiety and depression being 4-7 and 1.4% respectively, using a threshold score of 11 and above for the HADS subscales; the cut-off level first described by Zigmond and Snaith 15 for 'definite cases'. These levels and prevalence of both anxiety and depression are similar to population norms for UK men, not matched for age, 19 as well as to other reports of PSA screening 4,11 and from men with a diagnosis of early prostate cancer. 5 However, a recent review of the validity of the HADS stated that an optimal balance between sensitivity and specificity (0.80 each) for both HADS-A and HADS-D could be achieved by using a cut-off score of 8 þ .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The level as well as prevalence of depression was lower than of anxiety, with the prevalence of anxiety and depression being 4-7 and 1.4% respectively, using a threshold score of 11 and above for the HADS subscales; the cut-off level first described by Zigmond and Snaith 15 for 'definite cases'. These levels and prevalence of both anxiety and depression are similar to population norms for UK men, not matched for age, 19 as well as to other reports of PSA screening 4,11 and from men with a diagnosis of early prostate cancer. 5 However, a recent review of the validity of the HADS stated that an optimal balance between sensitivity and specificity (0.80 each) for both HADS-A and HADS-D could be achieved by using a cut-off score of 8 þ .…”
Section: Discussionsupporting
confidence: 84%
“…There is a high incidence of psychiatric disturbance reported in women who were recently diagnosed with breast cancer. 1 There have been conflicting reports however, with regard to the prevalence of mental health disturbance in men being investigated and treated for prostate cancer; with some studies reporting a high (50-64%) prevalence of anxiety, 2,3 whereas others report low levels in men being investigated 4 or treated for early localized prostate cancer 5 that are no different from those of a matched normal population. In addition, other reports suggest that men with advanced prostate cancer had significantly greater psychological distress as compared to those with early stage disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier longitudinal study of men being screened for prostate cancer, Gustafsson et al (1995) reported that cortisol level (indicating the degree of emotional stress) was highest immediately before being informed of the biopsy result, although levels decreased somewhat 2 weeks later in those who received a benign biopsy result. Other studies have concluded that testing for prostate cancer had little or no effect on men's psychological health (Brindle et al, 2006;Awsare et al, 2008). These studies relied on the Hospital Anxiety and Depression Scale (HADS) (Zigmond and Snaith, 1983), which was designed to detect clinical cases of anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in negative mood have been found in studies of women with abnormal but benign results for breast (Lowe et al, 1999;Aro et al, 2000) and ovarian (Andrykowski et al, 2004) cancer. Although studies of men undergoing PSA testing have shown no significant effect on anxiety for those receiving an abnormal PSA result (Essink-Bot et al, 1998;Brindle et al, 2006;Carlsson et al, 2007), it has been reported that those who receive a benign biopsy have thought and worried more about prostate cancer (McNaughtonCollins et al, 2004;Fowler et al, 2006;Katz et al, 2007). However, these latter studies were small and relied on unvalidated measures for these outcomes.…”
mentioning
confidence: 99%